Analisis Pendekatan Stimulus-Organism-Response Terhadap Adopsi M-Banking Syariah dengan Artificial Intelligence: Sebuah Bukti Empiris Generasi Z - Asgar; A Jaatsiyah Fath Falaq Am Nur; Mohd Shahril (Program Studi Magister Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Sunan Kalijaga, 2023)
Sharia m-banking users are increasingly rising among the Indonesian people. This study aims to analyze the stimulus-organism-response (S-O-R) approach to the adoption of Islamic m-banking with artificial intelligence among Generation Z. This paper contributes to or enriches the behavior of Islamic m-banking adoption with artificial intelligence Which of course is expected to be a consideration in the formulation of policies for stakeholders including Islamic financial institutions. This research is a type of field research using quantitative methods. Data collection using questionnaires was conducted online through Google Forms. Analysis with PLS-SEM using Smart-PLS with a sample of 100 respondents spread across several regions in South Sulawesi. The respondents were determined by the main criteria, namely Muslims aged 11-26 years who represent Generation Z. The results showed that perceived usability and perceived intelligence positively affect trust. In addition, perceived usability positively affects attitude, while trust and attitude positively affect the adoption of Islamic m-banking. However, unlike the case with perceived intelligence, service quality, and security do not significantly affect attitude, besides that service quality and security do not significantly affect trust. Meanwhile, the small impact produced by these factors. In addition, other factors have a greater influence on attitudes and beliefs in adopting Islamic m-banking-AI.